Pengaruh Indeks Pembangunan Manusia (IPM), Kemiskinan, Pengangguran Terhadap Pertumbuhan Ekonomi di Provinsi Aceh - Farathika Putri Utami (Fakultas Ekonomi Universitas Samudra, 2020)
This research was conducted to determine the relationship of the Human Development Index (HDI), Poverty, and Unemployment to the Economy in Aceh Province. The data used are data on the Human Development Index, Poverty, and Unemployment Rates for the Economy in 2008-2019 obtained from the Central Statistics Agency of Aceh Province. This research uses quantitative methods using simple linear regression analysis techniques. The value of r-squared (R2) is 0.952024 so that the Coefficient of Determination is 95.2024%, it can be concluded that it is related to the strong relationship between the Human Development Index, Poverty, Unemployment variables on economic growth in Aceh Province. These results indicate the Human Development Index Poverty Rate and Unemployment Rate affect the Economy in Aceh Province by 95.2024% and the remaining 4.7916% is needed by other variables that are not supported in this study. T-test results in Prob value <α 5% (0,0001 <0.05) can be recognized as the Human Development Index significantly influencing the economic debate in Aceh Province. On the Poverty variable the value of Prob <α 5% (0,0001 <0.05) can be recognized that Poverty has a significant influence on the Economy in Aceh Province. On the variable purchase value Prob <α 5% (0.0012 <0.05) F test results probability value (F statistic) <α 5% (0.000013 <0.005) can be approved simultaneously Human Development Index, Poverty and Unemployment influence significant to Economic studies in Aceh Province.